2012
DOI: 10.1055/s-0032-1324696
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Conventional Treatment for Patent Ductus Arteriosus in Preterm Infants

Abstract: We did not find any statistically significant differences in the clinical features of the two treatment groups, nor in the main efficacy, morbidity, and mortality results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Van Overmeire et al (38) reported that early treatment at postnatal day 3 was associated with more renal side effects without any advantage in respiratory or major outcomes. Candel-Pau et al (39) performed routine echocardiography within 48 hours after birth in infants < 29 weeks of gestation, and if the PDA diameter/weight ≥ 1.4 mm/kg and/or the LA/Ao ratio ≥ 1.4, indomethacin treatment was done. However, when they compared the frequency of secondary ligation, mortality and major preterm morbidities between such an early treatment group and the conventional treatment group, there were no significant differences like our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Van Overmeire et al (38) reported that early treatment at postnatal day 3 was associated with more renal side effects without any advantage in respiratory or major outcomes. Candel-Pau et al (39) performed routine echocardiography within 48 hours after birth in infants < 29 weeks of gestation, and if the PDA diameter/weight ≥ 1.4 mm/kg and/or the LA/Ao ratio ≥ 1.4, indomethacin treatment was done. However, when they compared the frequency of secondary ligation, mortality and major preterm morbidities between such an early treatment group and the conventional treatment group, there were no significant differences like our study results.…”
Section: Discussionmentioning
confidence: 99%